Development of nerve conduit using decellularized human umbilical cord artery seeded with Centella asiatica induced-neurodifferentiated human mesenchymal stem cell - Hanita Mohd Hussin; Ruszymah Hj Idrus; Yogeswaran Lokanathan (Penerbit Universiti Kebangsaan Malaysia, 2018)
Various natural biological conduits have been investigated to bridge peripheral nerve injury especially in critical gap (greater than 3 cm in human). Autograft, the current gold standard, has several drawbacks including limited availability of donor graft, donor-site morbidity and mismatch in size in clinical practices. The aim of this study was to analyze the development of nerve conduit using decellularized human umbilical cord (HUC) artery seeded with neurodifferentiated human MSCs (ndMSCs) in bridging peripheral nerve gap. Artery conduits obtained from HUC were decellularized to remove native cells (n=3), then characterized by Hematoxylin and Eosin (H&E) staining and nuclei counterstaining with DAPI. The decellularized artery conduit was measured for every 2 weeks until 12 weeks. Next, mesenchymal stem cells (MSCs) were differentiated into neural lineage using 400 μg/mL of Centella asiatica. Then, 1.5×106 of MSCs or ndMSCs were seeded into decellularized artery conduit to study cell attachment. H&E staining and nuclei counterstaining with DAPI showed that all cellular components were removed from the HUC arteries. The decellularized artery conduit did not collapse and the lumen remained rigid for 12 weeks. Immunocytochemistry analysis with neural markers namely S100β, P75 NGFR, MBP and GFAP showed that MSCs had differentiated into neural lineage cells. H&E staining showed that the seeded MSCs and ndMSCs attached to the lumen of the conduits as early as 2 days. In conclusion, this study showed that nerve conduit using decellularized HUC artery seeded with neurodifferentiated human MSCs was successfully developed and have the potential to bridge critical nerve gap.